(untitled) (Journal of Economic Research & Business Administration, 2016)
Project management Kazakh experts underserved pay attention to strategic project management organization for scientific and methodologi-cal level. Integration of project management systems are not considered as an organizational process, requiring a long lead time , and all the more as the process of improving enterprise efficiency . Today project management with the international standards and certi-fication became the bridge between Kazakhstan and the developed coun-tries. In turn it influences the level of competitiveness of the country. Use of methodology of project management effectively influences develop-ment industrial and innovative strategy of Kazakhstan.